(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The paper discusses some specific features related to the practical training of students of the Technical University of Gabrovo (Bulgaria) in some specific companies.